Contribution of tiller age category to herbage accumulation of Marandu palisadegrass under two fertilization regimes - Santos, Manoel Eduardo Rozalino; Carvalho, Angélica Nunes; Paiva, Adenilson José; Carvalho, Bruno Humberto Rezende; Borges, Gustavo Segatto; Silva, Simone Pedro da; Oliveira, Davi Moraes; Oliveira, Dallety Haloma Alves Miler de (Semina: Ciências Agrárias, 2022)
Based on the hypothesis that climate and fertilizers influence the proportion of tiller age categories in the canopy and, consequently, in herbage accumulation, the objective of this study was to determine the population density and the contribution of tiller age categories for herbage accumulation of Urochloa brizantha cv. Marandu during the year and in response to phosphate and nitrogen fertilization. The treatments consisted of two fertilization strategies: low and high fertilization and three tiller ages (young, mature and old), evaluated at four times of the year: winter, early and late spring, and summer. The total number of tillers and the proportion of young tillers were higher in late spring and summer. The growth and herbage accumulation rates showed a typical seasonal pattern and were higher in the canopy under high fertilization. Old tillers contributed more to control the total stem growth rate, as well as the canopy senescence rate. The highest percentage of young tillers is related to the high herbage accumulation in the Marandu palisadegrass canopy.